Influence of Low Temperature Storage and Ultrasonic Treatment of Placenta on Its Extracts Antioxidant Properties - Rozanova, Svetlana L.; Naumenko, Yevgeniya I.; Nardid, Eduard O. (Problems of Cryobiology and Cryomedicine, 2015)
The experimental data concerning evaluation of low temperature storage and ways of placenta extract obtaining influences on human placenta extract (HPE) antioxidant properties are provided. HPE antioxidant properties were estimated by capacity to reduce the ferric iron and ABTS+ radical, to chelate ferrous ions, by phenolic compound content and the value of catalase and superoxid dismutase activity. Six-month placentae storage at â€“196Â°Ð¡ has been shown not to affect HPE antioxidant activity. Moreover ultrasonic wave’s application during obtaining of HPE either decreases the time of extraction or is effective factor of extracts’ antioxidant properties preservation. Probl Cryobiol Cryomed 2015; 25(3):255-265